Economic and operational feasibility study : conversion to electric bus for Gray Line's airport route - Carpico,Kimberly Ann, 1980- (2018)
Widespread adoption of electric buses could take advantage of Iceland’s low-carbon energy mix and simultaneously help Iceland reach its objective of reducing greenhouse gas emissions. The purpose of this project was to conduct an operational and economic feasibility study for the addition of an electric bus to Gray Line’s Airport Express Route. This route provides transportation to and from Keflavik International Airport to Reykjavik. For the study we chose an BYD C9 electric bus as a candidate to replace the Volvo Sidreal 2000 diesel bus. The C9 electric bus performed nearly identical to the diesel bus in their current fleet, with no need for additional labor hours or changes in scheduled stops or frequency of stops. Minimal changes to the existing operational structure were necessary to utilize the electric bus for this route: (1) To ensure the battery of the electric bus was always sufficiently powered, it needed to be charged one hour at each end of the 51.6 kilometer trip to and from the airport by taking advantage of the already scheduled one-hour breaks in their current structure and (2) Arriving buses on each end of the trip need to form a horizontal row for access to the charging stations instead of the line formation currently used. An economic feasibility study examined the costs of three possible scenarios for the Airport Express Route in order to determine which scenario had the least inherent risk and therefore represented the best option. The three scenarios analyzed were the business as usual scenario in which the current 2013 Volvo Sidreal 2000 diesel bus is used, the scenario in which the BYD C9 electric bus is used accounting for half the cost of a charging station per bus, and the scenario in which the BYD C9 electric bus is used without the associated cost of charging stations. Accounting for the accumulated cost as a function of years, the cost of the electric bus without the needed charging stations broke-even with the NPV of the diesel bus in the 8th year. The project with the necessary ...